Art Under The Gun: The Role of Symbols Especially the Key in Contemporary Palestinian Art - Zoghi, Neda; Mohd Nor, Mohd Roslan; Abdul Hamid, Ahmad Faisal (Journal Al-Muqaddimah, 2019)
The art of Palestine, especially painting, has focused in recent decades on symbolism with value concepts, although it has experienced indirect effects of Western modernism. Palestinian painting symbols, which include a wide range of elements and phenomena, are, in some cases, consistent with common themes and sometimes are for Palestinian artists due to specific circumstances, as well as political and religious conditions. Meanwhile, some motifs have a special expressive capacity. Researches on the art of Palestine show that since the birth of Israel, some of the motifs have exerted a role and even beyond a painting as a symbol and dynamic expression of Palestinian art, and the Palestinians found them a model of national ownership expropriation and confiscation of their property. The specific conditions of Palestine have led to the emergence of resistance culture and art; and in the present paper, it is attempted to refer to the contemporary Palestinian painting to examine the element of resistance and its symbols, especially the key symbol in the contemporary Palestine art.